Current Clinical Approach of Nosocomial Clostridium difficileInfection - Liwang, Frans; Sinto, Robert (Jurnal Penyakit Dalam Indonesia, 2021)
Hospital-acquired Clostridium difficile infection (CDI) has become one of the global threats because the incidence has increased in recent decades. This nosocomial infection is closely related to antibiotic use in health services and is commonly found in the elderly. Antibiotics can promote colonization and CDI by intestinal microbiota dysbiosis and complex innate immune system activation. The manifestation also has a wide spectrum, ranging from mild diarrhea to fulminant colonic mucosal necrosis. Given that not all colonized subjects will be infected, further investigations such as toxigenic culture, nucleic-acid detection, and stool immunologic tests are only useful in symptomatic cases. In all CDI cases, an effort to control and prevent infections, including rational use of antibiotics, is warranted. Besides the use of antibiotics to eradicate the bacteria, surgery is often indicated in fulminant cases—another novel therapy for recurrent CDI as follows fecal microbiota transplantation, antitoxin antibody, and novel antibiotics.